2010
DOI: 10.1124/jpet.110.172957
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-((2-(trifluoromethyl)-3-hydroxy-4-(isobutyryl)phenoxy)methyl)benzyl)-1-methyl-1H-imidazole-4-carboxamide (THIIC), a Novel Metabotropic Glutamate 2 Potentiator with Potential Anxiolytic/Antidepressant Properties: In Vivo Profiling Suggests a Link between Behavioral and Central Nervous System Neurochemical Changes

Abstract: The normalization of excessive glutamatergic neurotransmission through the activation of metabotropic glutamate 2 (mGlu2) receptors may have therapeutic potential in a variety of psychiatric disorders, including anxiety/depression and schizophrenia. Here, we characterize the pharmacological properties of N- (4-((2-(trifluoromethyl)-3-hydroxy-4-(isobutyryl)phenoxy)methyl)benzyl)-1-methyl-1H-imidazole-4-carboxamide (THIIC), a structurally novel, potent, and selective allosteric potentiator of human and rat mGlu2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 35 publications
(40 reference statements)
4
68
0
1
Order By: Relevance
“…The lack of subtype-selectivity of MGS0039 and LY379268 may confound the interpretation of these findings. Recent evidence shows that a selective mGlu2 receptor enhancer produces antidepressant effects (45), and here, LAC relieved depressive symptoms by selectively inducing mGlu2 receptors. A potential involvement of mGlu3 receptors in the pathophysiology of depression is suggested by the association between a polymorphic variant of Grm3 (the gene encoding the mGlu3 receptor) and MDD (46).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of subtype-selectivity of MGS0039 and LY379268 may confound the interpretation of these findings. Recent evidence shows that a selective mGlu2 receptor enhancer produces antidepressant effects (45), and here, LAC relieved depressive symptoms by selectively inducing mGlu2 receptors. A potential involvement of mGlu3 receptors in the pathophysiology of depression is suggested by the association between a polymorphic variant of Grm3 (the gene encoding the mGlu3 receptor) and MDD (46).…”
Section: Discussionmentioning
confidence: 99%
“…These derivatives are exemplified with compound 9, as a potent mGluR2 PAM with an EC 50 value of 26 nM in FLIPR assay. A detailed in vivo profile of this compound, also known as THIIC, was given in a separate literature [47]. …”
Section: Arylketonesmentioning
confidence: 99%
“…The compound was shown to be an effective anxiolytic, but not an antidepressant agent after peripheral administration in animal studies (Klodzinska et al, 1999). However, data on the antidepressant action of a novel mGlu 2 receptor potentiator THIIC (Fell et al, 2011) was recently reported, creating a hope for the antidepressant-like action for subtype selective agonists/PAMs. Table 3 a number of experiments described the antidepressant-like activity of ligands of the mGlu 2/3 receptors.…”
Section: The Role Of Group II Mglu Receptors In the Mechanism Of Actimentioning
confidence: 99%